Relationship between husband support, maternal knowledge, and pregnancy exercise participation among pregnant women: A cross-sectional study - Ramayani Ramayani; Tamela Zahra; Siti Yuriah (School of Health Sciences Al-Ma'arif, 2026)
Background: Pregnancy exercise is a safe form of physical activity during pregnancy and contributes to maternal physical and psychological readiness for childbirth. However, pregnant women’s participation in pregnancy exercise may be influenced by several factors, including husband support and maternal knowledge regarding its benefits. A preliminary study at TPMB Bdn. Roslina, S.Keb indicated that several pregnant women had limited knowledge of pregnancy exercise and lacked adequate support from their husbands . Objective: This study aimed to analyze the relationship between husband support, maternal knowledge, and pregnancy exercise participation among pregnant women. Methods: This study employed a cross-sectional design. The sample consisted of 50 pregnant women in the second and third trimesters selected using accidental sampling. Data were collected through direct interviews using questionnaires measuring husband support and maternal knowledge of pregnancy exercise. Univariate and bivariate analyses were conducted using the Chi-square test with SPSS . Results: Of the 50 respondents, 33 pregnant women (66.0%) participated in pregnancy exercise, 29 respondents (58.0%) received husband support, and 31 respondents (62.0%) had good knowledge of pregnancy exercise. Bivariate analysis showed a significant relationship between husband support and pregnancy exercise participation (p < 0.001). Maternal knowledge was also significantly associated with pregnancy exercise participation (p < 0.001). Conclusion: Husband support and maternal knowledge were significantly associated with pregnancy exercise participation among pregnant women. Strengthening husband involvement and health education delivered by midwives may improve pregnant women’s participation in pregnancy exercise programs.